Matthys-Colle collection. (Deurle : Museum Dhondt-Dhaenens, 2007)
Andre, Carl ; Appel, Karel ; Arman ; Art & Language ; Barry, Robert ; Bellmer, Hans ; Bochner, Mel ; Brecht, George ; Brouwn, Stanley ; Buren, Daniel ; Charlton, Alan ; Christo ; de Cordier, Thierry ; Cragg, Tony (Anthony) ; Darboven, Hanne ; Dibbets, Jan ; van Elk, Ger ; Fisher, Joel ; Riverhead (New York) ; François, Michel ; Gilbert & George ; Gnoli, Domenico ; Huebler, Douglas ; Iglesias, Cristina ; Jorn, Asger ; Judd, Donald ; Kawara, On ; Kelley, Mike ; De Keyser, Raoul ; Klapheck, Konrad ; Klingelhöller, Harald ; Kosuth, Joseph ; Kounellis, Jannis ; Kudo, Tetsumi ; LeWitt, Sol ; Lichtenstein, Roy ; Lohaus, Bernd ; Long, Richard ; Magritte, René ; Mangold, Robert ; McCollum, Allan ; Merz, Mario ; Muñoz, Juan ; Nauman, Bruce ; Oldenburg, Claes ; Oppenheim, Dennis ; Pistoletto, Michelangelo ; Raynaud, Jean Pierre ; Rosenquist, James ; Rückriem, Ulrich ; Ryman, Robert ; Schütte, Thomas ; Tinguely, Jean ; Toroni, Niele ; Twombly, Cy ; Vercruysse, Jan ; Verheyen, Jef ; Vermeiren, Didier ; Visser, Carel ; Warhol, Andy ; Weiner, Lawrence ; Wesselmann, Tom ; West, Franz
Engelse titel, Engelse en Nederlandse tekst
boek
Keywords: Matthys-Colle